Towards Responsible Narratives in a More-than-Human World: Re-Storying Histories of Education - Priem, Karin; Keynes, Matthew R. (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2024)
When futures are disconnected from the past due to disaster and disruption, how do we study and story educational histories and to what ends? The role of education as a motor of technological progress facilitating imagined human sovereignty seems to have lost its persuasive power in creating better futures for all. Therefore, this Special Issue asks historians of education to acknowledge non-Western and Indigenous knowledge paradigms, education systems, and perspectives that have sustained peaceful and healthy ecological systems for millennia. Historians of education can bring into view the different and alternative kinds of knowledge and geo-ecological relationships future generations may want to revive and develop. Furthermore, historians can attend to human histories as a geological force and embrace diversity and decentralisation of knowledge within and against established practices of academic knowledge production.